Uncertainty and scale interactions in ocean ensembles: from seasonal forecasts to multi-decadal climate predictions - Zanna, L; Brankart, J; Huber, M; Leroux, S; Penduff, T; Williams, P (Wiley, 2018)
The ocean plays an important role in the climate system on timescales of weeks to centuries. Despite improvements in ocean models, dynamical processes involving multi‐scale interactions remain poorly represented, leading to errors in forecasts. We present recent advances in understanding, quantifying and representing of physical and numerical sources of uncertainty in novel regional and global ocean ensembles at different horizontal resolutions. At coarse‐resolution, uncertainty in 21st‐century projections of the upper overturning cell in the Atlantic is mostly a result of buoyancy fluxes, while the uncertainty in projections of the bottom cell is driven equally by both wind and buoyancy flux uncertainty. In addition, freshwater and heat fluxes are the largest contributors to Atlantic Ocean Heat Content regional projections and to its uncertainty, mostly as a result of uncertain ocean circulation projections. At both coarse‐ and eddy‐permitting resolution, the unresolved stochastic temperature and salinity fluctuations can lead to significant changes in large‐scale density across the Gulf Stream front, therefore leading to major changes in large‐scale transport. These perturbations can have an impact on the ensemble spread on monthly time‐scales and subsequently interact non‐linearly with the dynamics of the flow generating chaotic variability on multi‐annual timescales. In the Gulf Stream region, the ratio of chaotic variability to atmospheric‐forced variability in meridional heat transport is larger than 50% on timescales shorter than 2 years; while between 40 and 48 ∘S the ratio exceeds 50% on on time scales up to 28 years. Based on these simulations, we show that air‐sea interaction and ocean sub‐grid eddies remain an important source of error for simulating and predicting ocean circulation, sea level, and heat uptake on a range of spatial and temporal scales. We discuss how further refinement of these ensembles can help us assess the relative importance of oceanic versus atmospheric uncertainty in weather and climate.